A computerized indicator for surgical site infection (SSI) assessment after total hip or total knee replacement: The French ISO-ORTHO indicator. (9th September 2022) - Grammatico-Guillon, Leslie; Miliani, Katiuska; Banaei-Bouchareb, Linda; Solomiac, Agnès; Sambour, Jessica; May-Michelangeli, Laetitia; Astagneau, Pascal
Abstract: Objective: The French National Authority for Health (HAS), with a multidisciplinary working group, developed an indicator 'ISO-ORTHO' to assess surgical site infections (SSIs) after total hip arthroplasty or total knee arthroplasty (THA/TKA) based on the hospital discharge database. We present the ISO-ORTHO indicator designed for SSI automated detection and its relevance for quality improvement and hospital benchmarks. Methods: The algorithm is based on a combination of International Statistical Classification of Diseases, Tenth Revision (ICD-10) and procedure codes of the hospital stay. The target population was selected among adult patients who had a THA or TKA between January 1, 2017, and September 30, 2017. Patients at very high risk of SSI and/or with SSI not related to hospital care were excluded. We searched databases for SSIs up to 3 months after THA/TKA. The standardized infection ratio (SIR) of observed versus expected SSIs was calculated (logistic regression) and displayed as funnel plot with 2 and 3 standard deviations (SD) after adjustment for 13 factors known to increase SSI risk. Results: In total, 790 hospitals and 139, 926 THA/TKA stays were assessed; 1, 253 SSI were detected in the 473 included hospitals (incidence, 0.9%: 1.0% for THA, 0.80% for TKA). The SSI rate was significantly higher in males (1.2%), in patients with previous osteo-articular infection (4.4%), and those with cancer (2.3%), obesity, or diabetes. Most hospitals (89.9%) were within 2 SD; however, 12 hospitals were classified as outliers at more than +3 SD (1.6% of facilities), and 59 hospitals (7.9%) were outliers between +2 SD and +3 SD. Conclusion: ISO-ORTHO is a relevant indicator for automated surveillance; it can provide hospitals a metric for SSI assessment that may contribute to improving patient outcomes.